The ethics of abortion: pro-life vs. pro-choice - Baird, Robert M.; Rosenbaum, Stuart E. (Contemporary issues, 1993)
Abortion / Richard Selzer -- The bad old days / Ellen Messer & Kathryn E. May -- The abortion orphans / Anna Quindlen -- Roe v. Wade -- Webster v. Reproduction Health Services -- Planned Parenthood of Southeastern Pennsylvania v. Casey -- Again, a struggle for the soul of the court / Robert H. Bork -- On the origins of privacy / Melvin L. Wulf -- The center holds / Ronald Dworkin -- Abortion and the sexual agenda / Sidney Callahan -- Abortion and feminism -- Sally Markowitz -- We must rescue them / Gary Leber -- A Catholic theologian at an abortion clinic / Daniel C. Maguire -- Why abortion is a religious issue / Stanley Hauerwas -- Personhood, the Bible, and abortion / Paul D. Simmons -- Life in the tragic dimension / Roger A. Paynter -- A defense of abortion / Judith Jarvis Thomson -- Nature as demonic in Thomson's defense of abortion / John T. Wilcox --On the moral and legal status of abortion status of abortion / Mary Anne Warren -- An appeal for consistency / Harry J. Gensler -- The fetus and fundamental rights / Joan C. Callahan -- In an embryo a person / Charles A. Gardner